(3GdYeOIs - (3GdMSf Hf QTjb GdbjQhGfj, CHh Ydj , GHf QTjb,J (B463 (3g` s ((3CMeO Hf SYjO GdUfgGLi s)
(3ChdgG (B:s
(3GdMeO ddg Cgd GdMeO heSJMbI CeG HYO , aEf CMb ef Lfi JeQ GdBOGH ef YQa ddYde Mbg cGdGSjO GdCeLO CHj GdMSf Ydi Hf CHj GdQLGd hEf de CYdb ef GddYe EdG HMGTjI s
(3BNQgG (B:s
(3MHjHi ZOkG dGTc ajg ehOY ahGddg dG COQi Hg cja CUfY Je GdLRA GdChd ef cJGH GdYeOI jJdhg GdKGfi HGH GdJaSjQ hgh Cf jSJhai GdTGYQ TQM GfJgi HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3fSNI CNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B225s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1169s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs